Classification of renal cell tumors - current concepts and use of ancillary tests: recommendations of the Brazilian Society of Pathology - Daniel Abensur Athanazio; Luciana Schultz Amorim; Isabela Werneck da Cunha; Katia Ramos Moreira Leite; Alexandre Rolim da Paz; Regina de Paula Xavier Gomes; Fabio Rocha Fernandes Tavora; Sheila Friedrich Faraj; Marcela Santos Cavalcanti; Stephania Martins Bezerra (BMC, 2021)
Abstract Classification of renal cell carcinomas has become more challenging. The 2016 WHO classification included 14 different subtypes and 4 emerging/provisional entities, and recent literature indicates new entities to be incorporated. Nomenclature is based on cytoplasmic appearance, architecture, combination of morphologies, anatomic location, underlying disease, familial syndromes, and specific genetic alterations. Immunohistochemistry is useful in selected cases while it can be insufficient in entities that require molecular confirmation of a specific gene alteration. The aim of these recommendations is to provide a reasonable and optimized approach for the use of ancillary tests in subtyping renal tumors, particularly in resource-limited settings.